Sex-specific Difference of Hippocampal Synaptic Plasticity in Response to Sex Neurosteroids. (4th December 2019) - Brandt, Nicola; Vierk, Ricardo; Fester, Lars; Anstötz, Max; Zhou, Lepu; Heilmann, Lukas F; Kind, Simon; Steffen, Paul; Rune, Gabriele M
Abstract: Numerous studies provide increasing evidence, which supports the ideas that every cell in the brain of males may differ from those in females due to differences in sex chromosome complement as well as in response to hormonal effects. In this study, we address the question as to whether actions of neurosteroids, thus steroids, which are synthesized and function within the brain, contribute to sex-specific hippocampal synaptic plasticity. We have previously shown that predominantly in the female hippocampus, does inhibition of the conversion of testosterone to estradiol affect synaptic transmission. In this study, we show that testosterone and its metabolite dihydrotestosterone are essential for hippocampal synaptic transmission specifically in males. This also holds true for the density of mushroom spines and of spine synapses. We obtained similar sex-dependent results using primary hippocampal cultures of male and female animals. Since these cultures originated from perinatal animals, our findings argue for sex-dependent differentiation of hippocampal neurons regarding their responsiveness to sex neurosteroids up to birth, which persist during adulthood. Hence, our in vitro findings may point to a developmental effect either directly induced by sex chromosomes or indirectly by fetal testosterone secretion during the perinatal critical period, when developmental sexual priming takes place.